The English and Irish of Alicante and Cartagena during the Wars of Succession of Monferrato and Austria (1628-1748) - Montojo Montojo, Vicente (Americanía: Revista de Estudios Latinoamericanos, 2019)
The importance of the penetration of the English in the Spanish Mediterranean of the seventeenth and eighteenth centuries was noticed only in Alicante by Martínez Ruiz and Gauci, but denied to Cartagena de Levante, so this text will demonstrate the results of research on its installation in Cartagena and in Benicarló and Vinaroz, ports in the north of the Kingdom of Valencia, whose merchants had commercial relations with those of Alicante and Cartagena, due to the traffic and transport of wine. A fundamental point has been the archival and heuristic methodology, since both the study of the Board of Dependencies and Foreign Businesses in Madrid, as well as that of the Consulate and Commercial Court of Valencia, have allowed an account of the directions and flows of the commercial business and litigation derived from the merchants of the different populations mentioned.